Assessment of the Correlation between Appointment Scheduling and Patient Satisfaction in a Pediatric Dental Setup - Amar N. Katre (International Journal of Dentistry)
Introduction. The practice of modern pediatric dentistry requires delivery of quality care in combination with adherence to excellent business as well as time management principles. A definite appointment schedule should be presented to the parents on the first or second appointment. More importantly, the prescribed schedule should be followed to the best of the professional abilities of the pediatric dentist. Aims. The aim of the study was to assess the co-relation between appointment scheduling and patient satisfaction in a pediatric dental setup with the objective of understanding the parameters related to appointment scheduling to increase patient satisfaction. Method. A total of 40 patients, who visited the Department of Pediatric and Preventive Dentistry, YMT Dental College & Hospital, for dental treatment were selected on a random basis. A questionnaire with a set of 6 questions with a rating scale of 1–5 to assess the patient satisfaction related to appointment scheduling was prepared. Results. A significant number of the patients were happy with the existing appointment scheduling system barring a few exceptions.